Inevitability of European Travelogues in the Socio-Cultural Studies of Later Medieval Maharashtra - Premsagar, Pankajkumar S. (Mediterranean Journal of Social Sciences, 2012)
After the Arrival of Portuguese sailor Vasco-de-Gama in India, many foreign travelers has been visited India. The ratio ofEuropean travelers was more than other foreign travelers in the post medieval period for visiting India. European travelers had keenlyand minutely observed and what they had observed, heard; they have noted it down carefully. They had noted down the informationabout the cities which they had visited; the customs and traditions, believes and blind-believes, birds and animals, weights andmeasurements.